Chloride Binding Capacity and Water Absorption of Mortar Containing Fly Ash, Limestone Powder, and Expansive Additive - Prak, Lyna; Sumranwanich, Taweechai (Frontiers in Engineering Innovation Research, 2020)
This paper aims to study the chloride binding capacity and water absorption of mortar containing fly ash (FA), limestone powder (LP), and expansive additive (EA). Portland cement Type I was used as the main cementitious material. The water to binder ratio was kept at the ratio of 0.40 and 0.50. FA and LP partially replaced the cement at percentages ranging from 5% to 30%; EA replaced the binder at 10%. The chloride penetration test of mortars was conducted at the chloride exposure period of 91 days. The water absorption of mortars was done at the age of 28 days after curing. From the results, it was found that chloride binding capacity of FA mortars and EA mortars was higher than that of cement-only mortars, while chloride binding capacity of LP mortars was lower than that of cement-only mortars. Increasing the LP to binder ratio resulted in the reduction of chloride binding capacity of mortars. The chloride binding capacity of FA mortars was highest. Moreover, the water absorption of Mortar with FA, LP, and EA was higher than that of the cement-only mortars.